Stakeholder salience in public sector value co-creation. Issue 11 (2nd November 2019) - Best, Bernadette; Moffett, Sandra; McAdam, Rodney
ABSTRACT: This paper examines key determinants of stakeholder salience and how this impacts value co-creation at different stages and levels of a service context within a consortium of UK non-government inter-sectoral organizations delivering public services. It uses three empirical stages to illustrate how value is conceptualized by different stakeholders at different stages of a service context. It then examines how stakeholder identities, and attributes of stakeholder salience and behaviour impact value co-creation across a network of stakeholders resulting in value gains and/or challenges at different levels. Finally, it offers approaches enabling greater value, through the effective management of stakeholder salience.